Vertigo et Causa Hipertensi pada Perempuan Usia 58 Tahun: Studi Kasus Klinis dengan Evaluasi Gejala, Diagnosis, dan Terapi - Nur Sakinah Nasution; Manghfiroh Rahma Rafie; Siti Khadijah (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2026)
Vertigo is a clinical symptom that is often found and can be related to vestibular disorders or systemic conditions such as hypertension. The case report described a 58-year-old female patient who came in with complaints of dizziness that disappeared from 12 hours before admission to the hospital, accompanied by double vision, nausea, severe headache, flatulence, and stiffness of the left shoulder. Physical examination showed increased blood pressure and bidirectional nystagmus on neurological examination. Laboratory tests show mild electrolyte abnormalities and increased cholesterol. The patient was diagnosed with uncontrolled vestibular vertigo et causa hypertension and received intravenous fluid therapy, symptomatic therapy, antihypertensive therapy, and vestibular suppressants. Clinical improvements were obtained during follow-up. Education related to blood pressure control, medication adherence, and lifestyle changes such as low-salt diet settings and stress management is also provided to patients. In addition, periodic monitoring is required to prevent recurrence and further complications. This case emphasizes the importance of identifying hypertension as a contributing factor to vertigo as well as comprehensive management to improve patient outcomes and improve the quality of life of patients.